2024
DOI: 10.5132/eec.2016.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Quaternary Mixtures of Phenolic Compounds and Formulated Glyphosate to Microbial Community of River Water

Abstract: The toxicity of mixtures of formulated glyphosate, phenol, 4-chlorophenol and 2,4-dichlorophenol to river water microbial community was investigated using non specific dehydrogenase activity as endpoint. The microbial community was exposed to individual toxicant and quaternary mixture ratios at concentrations ranging from 50 mg L -1 to 3000 mg L -1 over 24 h. The ecological doses (EC 50 ) as estimated from logistic or hormesis dose-effect models were 1317.946 ± 51.460 mg L -1 , 1046.414 ± 65.534 mg L -1 , 85.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…[12] reported that glyphosate alters the soil texture and microbial diversity by reducing the microbial richness and increasing the population of phytopathogenic fungi. In another study, [13] reported additive interactions of formulated glyphosate with the phenolic compounds. Also, studies have proven that a greater amount of these pesticides do not end up in their intended locations and are dispersed into the ecosystem to non-target organisms through various mechanisms such as run off, erosion deposition by wind, biomagnification, and bioaccumulation [14].…”
Section: Glyphosatementioning
confidence: 99%
“…[12] reported that glyphosate alters the soil texture and microbial diversity by reducing the microbial richness and increasing the population of phytopathogenic fungi. In another study, [13] reported additive interactions of formulated glyphosate with the phenolic compounds. Also, studies have proven that a greater amount of these pesticides do not end up in their intended locations and are dispersed into the ecosystem to non-target organisms through various mechanisms such as run off, erosion deposition by wind, biomagnification, and bioaccumulation [14].…”
Section: Glyphosatementioning
confidence: 99%
“…The model was also used to study plant hormesis in response to herbicide application (Zelaya & Owen, 2005;Belz & Cedergreen, 2010). More recently, Nweke et al (2016) used the model to describe herbicide hormesis in microbial community of river water.…”
Section: Limitations Of Brain and Cousens Modelmentioning
confidence: 99%
“…This phenomenon termed 'hormesis' has been observed with all groups of living things for a wide range of endpoints. Hormesis is induced by physical and chemical stressors including phenolic compounds (Boyd et al, 1997;Sinclair et al 1999;Okolo et al 2007;Zaki et al, 2008;Nweke & Okpokwasili, 2010 a, b;Nweke et al, 2014Nweke et al, , 2015, perfluorinated carboxylic acids (Mulkiewicz et al, 2007), mycotoxins (Li et al, 2014;Wang et al, 2014), bacteriocins (Murado & Vázquez, 2010), antibiotics (Welch et al, 1946;Randall et al, 1947, Linares et al, 2006Migliore et al, 2010Migliore et al, , 2013, herbicides (Cedergreen 2008a,b;Cedergreen et al, 2009;Belz & Cedergreen, 2010;Cedergreen & Olesen, 2010;Belz et al, 2011;Belz & Leberle, 2012;Nweke et al, 2016), Wastewater (Hoffmann & Christofi, 2001;Nwanyanwu & Abu 2010), heavy metals (Christofi et al, 2002;Rodea-Palomares et al, 2009;Shen et al, 2009) and ionic liquids (Cho et al, 2007; either as individual or as mixtures. Hormesis was commonly observed in the toxicity test on luminescent bacteria (Christofi et al, 2002;Brack et al, 2003;Fulladosa et al, 2005;Deng et al, 2012;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Triplicate control tubes were prepared for each metal ion, giving a total of 12 controls. The cultures were incubated at room temperature (28 ± 2 o C) for 24 h. The extraction and quantification of TTC-formazan were done as described by Nweke et al (2016).…”
Section: Acute Toxicity Assaymentioning
confidence: 99%